The clarification of sugarcane juice and the use of CA-11 yeast produces better quality cachaça (Revista Ciência Agronômica, 2020)
Cachaça is the second most consumed alcoholic beverage in Brazil, obtained by distilling wine fromfermented sugarcane must, and has an alcohol content of 38 to 48% (v/v) at 20 ºC. The quality of the drink is affected bythe raw material used, the treatment of the juice, the type of yeast and the distillation process. The aim of this study was toevaluate the performance of two types of yeast (selected and pressed) and the prior physical and chemical treatment of thesugarcane juice on the quality of the cachaça. The experimental design was completely randomised with 9 replications. Theprimary treatment was represented by the must (obtained from clarified and non-clarified juice) and the secondary treatmentby the types of yeast (CA-11 and pressed biological). The microbiological behaviour of the yeast during fermentationwas evaluated together with the chemical composition of the wine and cachaça. The use of selected strains and the priortreatment of the juice resulted in better performance of the fermenting yeasts, producing distillates of suitable physical andchemical standards and quality.